2019
DOI: 10.5812/jjcdc.95530
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Incidence Analysis of Head and Neck Cancer Patients in Rural Areas of Sindh, Pakistan

Abstract: Background: Head and neck cancer is the most common malignancy in Sindh, Pakistan. The type of cancer can be observed in the oral cavity, lips, buccal mucosa, oropharynx, hypopharynx, nasopharynx, the floor of the mouth and hard palate in Sindh. , comprising 56% males and 44% females. The most common site of the head and neck tumors was the oral cavity (58%), followed by the tongue, tonsil, floor of the mouth, gum, hard palate, soft palate, and lips. Other sites of head and neck cancer were hypo-pharynx, nasop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In this study, commonly reported head and neck carcinomas were in the oral cavity (62.0%), followed by the oropharynx (24.0%), hypopharynx (5.5%), nasopharynx (5.0%), and larynx (3.5%). Similar patterns of head and neck carcinomas were reported in other Pakistani studies, including those from Waqar et al [ 20 ], who reported higher rates of oral cavity carcinoma (58.0%), followed by the hypopharynx (22.1%), nasopharynx (5.0%), oropharynx (5.0%), and larynx (4.0%). Aziz et al also reported high rates of oral cavity carcinoma (69.0%), followed by larynx (31.0%), and oropharyngeal [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, commonly reported head and neck carcinomas were in the oral cavity (62.0%), followed by the oropharynx (24.0%), hypopharynx (5.5%), nasopharynx (5.0%), and larynx (3.5%). Similar patterns of head and neck carcinomas were reported in other Pakistani studies, including those from Waqar et al [ 20 ], who reported higher rates of oral cavity carcinoma (58.0%), followed by the hypopharynx (22.1%), nasopharynx (5.0%), oropharynx (5.0%), and larynx (4.0%). Aziz et al also reported high rates of oral cavity carcinoma (69.0%), followed by larynx (31.0%), and oropharyngeal [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…The incidence rate of head and neck cancer is alarmingly high in Karachi, where most of this study’s patients lived in urban areas. Some of the more common reasons cited for the higher incidence and mortality rates here are low levels of education, poverty, and addictions, such as common use of smoking, betel nuts, pan, gutka, naswar, alcohol consumption, and so on [ 16 - 20 ]. In this study, commonly reported head and neck carcinomas were in the oral cavity (62.0%), followed by the oropharynx (24.0%), hypopharynx (5.5%), nasopharynx (5.0%), and larynx (3.5%).…”
Section: Discussionmentioning
confidence: 99%
“…7 A study was conducted by Waqar et al, there was a male predominance, with tumors of the oral cavity being the most common and 3% of them occurring in the salivary gland. 8 The West is reported to have a prevalence of 2.5-3 per 100,00 people per year of salivary gland tumors. They have a lower incidence of malignancy, with approximately 80% of them being benign.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancer (HNC) is the sixth most prevalent type of cancer globally, and it is especially common in some of the less developed nations. 1,2 Currently, standard treatments for HNCs are surgery and radiotherapy with or without chemotherapy, which are always associated with side effects during or after treatment. Oral mucositis and dry mouth are the most frequent side effects.…”
Section: Introductionmentioning
confidence: 99%